2021
DOI: 10.4103/wjtcm.wjtcm_54_21
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Prescription-Generating Models of Traditional Chinese Medicine Based on Deep Learning

Abstract: Objective: This study aimed to construct an intelligent prescription-generating (IPG) model based on deep-learning natural language processing (NLP) technology for multiple prescriptions in Chinese medicine. Materials and Methods: We selected the Treatise on Febrile Diseases and the Synopsis of Golden Chamber as basic datasets with EDA data augmentation, and the Yellow Emperor's Canon of Internal Medicine, the Classic of the Miraculous Pivot, and the Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…it is a classic prescription for the treatment of gout. [13] In this study, we found that the core active components of DGNTD in the treatment of gout include quercetin, kaempferol, formononetin, luteolin and wogonin. Quercetin is the active compound of Licorice (Gancao), Herba Artemisiae (Yinchen) and Sophora flavescens (Kushen), kaempferol is the active compound of Licorice (Gancao), Ginseng (Renshen) and Sophora flavescens (Kushen), formononetin is the active compound of Licorice (Gancao), Radix puerariae (Gegen) and Sophora flavescens (Kushen), luteolin is the active compound of Radix Atractylodis (Cangzhu), and baicalein is the active compound of Saposhnikoviae Radix (Fangfeng), Radix Atractylodis (Cangzhu) and Radix Scutellariae (Huangqin).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…it is a classic prescription for the treatment of gout. [13] In this study, we found that the core active components of DGNTD in the treatment of gout include quercetin, kaempferol, formononetin, luteolin and wogonin. Quercetin is the active compound of Licorice (Gancao), Herba Artemisiae (Yinchen) and Sophora flavescens (Kushen), kaempferol is the active compound of Licorice (Gancao), Ginseng (Renshen) and Sophora flavescens (Kushen), formononetin is the active compound of Licorice (Gancao), Radix puerariae (Gegen) and Sophora flavescens (Kushen), luteolin is the active compound of Radix Atractylodis (Cangzhu), and baicalein is the active compound of Saposhnikoviae Radix (Fangfeng), Radix Atractylodis (Cangzhu) and Radix Scutellariae (Huangqin).…”
Section: Discussionmentioning
confidence: 93%
“…DGNTD has been widely used in clinical treatment of gout in China and achieved satisfactory results. [12,13] Previous studies have shown that DGNTD can improve synovitis in arthritic rats by inhibiting synovial hyperplasia, infiltration of inflammatory cells, and destruction of cartilage and bone during inflammation. [14] Recently, DGNTD has been proved to effectively alleviate the degree of inflammatory swelling of paws in AGA mice, down-regulate the expression of inflammatory factors IL-1β, TNF-α and iNOSmRNA, and reduce the concentration of serum uric acid.…”
Section: Introductionmentioning
confidence: 99%
“…During the nursing intervention based on the continuity model, the self-developed multifunctional arm frame is used to properly elevate the affected limb and assist joint function rehabilitation training, so as to improve the functional rehabilitation effect of the affected upper limb and ultimately improve the quality of life. [21] Nursing intervention based on continuity model attaches importance to music therapeutic touch and music rehabilitation exercise, so that patients can carry out rehabilitation training accompanied by music, which does not rely on any drugs, and use the special relationship between music and people to improve the body's health status. As an ideal "natural therapy," musical therapeutic touch and musical rehabilitation exercise directly affect brain stem reticular structure, limbic system, and hypothalamus through the special physiological effect of music, stimulate pituitary secretion and release of endorphins, so as to effectively improve the rehabilitation effect of upper limb function and improve the quality of life.…”
Section: Effect Of Nursing Intervention Based On Continuity Model On ...mentioning
confidence: 99%
“…It would ensure the quality of medications and meet clinical needs by enhancing the intelligence and informatization of instruments on the existing technological foundation, achieving intelligent pharmaceutical manufacturing. [43] 3. Looking toward the future…”
Section: Smart Hospitals and Clinics Since The 1980s CM Hospitals Inmentioning
confidence: 99%